Reconstruction of radioactivity in semi-closed ocean systems using nuclear methods: a case study at North Cretan basin - Maniati, Zoi; Tsabaris, Christos; Androulakaki, Effrosyni; Alexakis, Stylianos; Manta, Kiki; Patiris, Dionisis; Kokkoris, Michael (HNPS Advances in Nuclear Physics, 2025)
A sediment core was collected using a box corer from the North Cretan deep basin, at a depth of 1500 m, in order to determine the rate of sedimentation, to measure the levels of radioactivity of 137Cs and to investigate potential past geophysical events. The activity concentrations of the radionuclides were measured in the laboratory by the gamma spectroscopy method using a High-Purity Germanium (HPGe) detector at the Marine Environmental Laboratory of HCMR. The sedimentation rate was calculated applying radio-dating models by both the 210Pb and the 137Cs methods. The low sedimentation in the studied area exhibited folded peaks of the Cs deposition due to Chernobyl and nuclear tests. The results of the measurements showed that Cs appeared in the first 4 cm of the sediment core and its activity concentration ranged from (6.66 ± 0.62) Bq kg-1 to (1.39 ± 0.28) Bq kg-1, with a value of (6.66 ± 0.62) Bq kg-1 on the surface sample. The sedimentation rate was estimated at (0.037 ± 0.007) cm y-1 with the 210Pb radiochronology model. Additionally, it was observed the signature of the volcanic eruption that took place close to Santorini Island (almost 300 years ago) was evident at around 10.5-11.0 cm. The deep basin of the North Cretan Sea, although it does not interact with the terrestrial environment, was affected by anthropogenic pressures, as well as by the footprint of natural hazards.